2012
DOI: 10.1007/s13197-012-0622-2
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of smoked buffalo rumen meat product treated with ginger extract

Abstract: Smoked buffalo rumen meat products were prepared from 3 times blade tenderized buffalo tripe with 5.0% ginger extract and were subjected to various physico-chemical parameters, microbial profile and sensory quality at 25 ± 1 °C under aerobic packaging. All physico-chemical parameters, microbial counts and sensory evaluation score of ginger extract treated buffalo rumen meat product were higher compared to control. pH, moisture content, thiobarbituric acid, tyrosine values, total plate, yeast and mould and stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…T2 and T3 had significantly higher ( P < 0.05) IMP concentration than T1, and T3 had the highest IMP concentration throughout the entire storage period. This might explain the results of Anandh & Lakshmanan (), who reported improvement in colour and appearance of buffalo meat treated with ginger extract. The ATP/IMP ratio of T3, coupled with the highest IMP concentration, suggested that postmortem glycolysis was more rapid in T1, T2 and T3 than in the control, which was evident by the lower pH value of T1, T2 and T3.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…T2 and T3 had significantly higher ( P < 0.05) IMP concentration than T1, and T3 had the highest IMP concentration throughout the entire storage period. This might explain the results of Anandh & Lakshmanan (), who reported improvement in colour and appearance of buffalo meat treated with ginger extract. The ATP/IMP ratio of T3, coupled with the highest IMP concentration, suggested that postmortem glycolysis was more rapid in T1, T2 and T3 than in the control, which was evident by the lower pH value of T1, T2 and T3.…”
Section: Resultsmentioning
confidence: 77%
“…Ginger extract is used typically as a condiment in household cooking. Anandh & Lakshmanan () claimed that ginger extract inhibited the increase in tyrosine and total plate count and improved the flavour score, colour and appearance of buffalo rumen meat; Mendiratta et al . () reported that ginger extract lowered thiobarbituric acid (TBA) values and microbial counts, improved sensory quality significantly and extended the shelf life of sheep meat; Naveena & Mendiratta () reported an improvement in the flavour score of hen meat treated with ginger extract.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking allows to incorporate different specie meats to obtain a high quality sensory sausages [ 79 ]. The sensory scores for smoked buffalo rumen meat products added with ginger extract were found to be within the acceptable limit during the storage period of 15 days [ 80 ]. Meat smoking enhances the sensory attributes but at the same time contaminates with carcinogenic residues such as polycyclic aromatic hydrocarbons or nitrosamines [ 72 , 81 , 82 ].…”
Section: Processingmentioning
confidence: 99%
“…It is mainly used as flavor inducing agent in several food and beverage products and is also well known for its medicinal properties [8]. The inclusion of ginger extracts in foods can prevent the occurrence of foodborne epidemic outbreaks due to its associated antimicrobial properties [9]. Besides being antimicrobial in nature, ginger is also known to possess antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%